2015
DOI: 10.1038/srep08049
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Lubrication of Ionic Surfaces Controlled via a Strong Electric Field

Abstract: Frictional forces arise whenever objects around us are set in motion. Controlling them in a rational manner means gaining leverage over mechanical energy losses and wear. This paper presents a way of manipulating nanoscale friction by means of in situ lubrication and interfacial electrochemistry. Water lubricant is directionally condensed from the vapor phase at a moving metal-ionic crystal interface by a strong confined electric field, thereby allowing friction to be tuned up or down via an applied bias. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…The author described the frequency dependence of friction in terms of the dynamic conformal change of PE ionization under the electric field. Recently, Strelcov et al reported that boundary lubrication properties can be actively controlled between an AFM tip and a salt surface when the relative humidity is above a certain threshold and a sufficiently strong electric field is applied [132]. A plausible mechanism was proposed that an ordered structure of electric double layer as a result of water condensation and dissolution of polarizable ions accounts for the reduction of friction force.…”
Section: Other Approaches For Active Control Of Boundary Lubricationmentioning
confidence: 99%
“…The author described the frequency dependence of friction in terms of the dynamic conformal change of PE ionization under the electric field. Recently, Strelcov et al reported that boundary lubrication properties can be actively controlled between an AFM tip and a salt surface when the relative humidity is above a certain threshold and a sufficiently strong electric field is applied [132]. A plausible mechanism was proposed that an ordered structure of electric double layer as a result of water condensation and dissolution of polarizable ions accounts for the reduction of friction force.…”
Section: Other Approaches For Active Control Of Boundary Lubricationmentioning
confidence: 99%
“…Both observations [88,92] indicate clearly that the positively charged (H + ) tip or substrate (electronic holes +) would induce high friction force [23].…”
Section: Quantum Friction: Charging and Isotopic Phonon Effectmentioning
confidence: 99%
“…In 1989, Krim and coworkers [6] found the friction coefficient of Krypton films on crystalline gold surfaces is lower when dry; adding a liquid film raises the coefficient by five times, instead. Applying electric field cross the contacting interface can also affect the coefficient of friction [23].…”
Section: Interface Phonons and Electronsmentioning
confidence: 99%
“…A similar setup is used for nanometer-scale material modifications [9][10][11]. Concentrated electric fields developed during voltage application in the tip-sample junction in a volume of a few tens of nanometers in size can be extremely strong -in excess of 10 8 V/m, which has been utilized to explore phenomena and material behaviors in strong electric fields, for example, nanoscale melting [12], electric-field-induced water condensation [13,14], water dissociation [15], nanoscale lubrication [16], and ionic conduction [17]. Such studies would highly benefit from knowledge of the electric field strength at the tip-sample contact through providing well-controlled stimulus as well as for correct interpretation and modeling of results.…”
Section: Introductionmentioning
confidence: 99%
“…Observation of effects associated with the large electric field in the tip-sample junction indirectly proves the large strength of the field (see, e.g., refs. [9,13,14,16]). However, currently there are no methods, which would allow measuring the electric field strength in the junction.…”
Section: Introductionmentioning
confidence: 99%